Soil Aggregate Stability: Its Evaluation and Relation to Organic Matter Constituents and Other Soil Properties - Teh, Christopher Boon Sung (1996)
The purpose of this study were: 1) to compare the aggregate stability of individual aggregate size fractions, 2) to determine the interrelationship and efficiency of several aggregate stability indices, and 3) to determine the relationship and importance of organic matter and other soil constituents on aggregate stability. To compare the aggregate stability of individual aggregate size fractions, a mathematical model was developed to estimate the breakdown of individual aggregate size fractions in the wet-sieving (using nested sieves) method. This model was validated and calibrated by comparing the estimation values to the actual aggregate breakdown values by paired sample t-test, linear regression and prediction error sum of squares. The average percentage of stable aggregates for all aggregate size fractions were represented in an index called average intact aggregates (AlA). Factor analysis was used to determine the interrelationship and efficiency of several aggregate stability indices. Aggregate stability of eight soil samples were measured with eight indices: percentage of water-stable aggregates >0.3 mm (WSA >0.3) and >0.5 mm (WSA >0.5), AlA, water-dispersible clay (WDC), waterdispersible clay and silt (WDCS), mean weight diameter after wet-sieving (MWDw), turbidity percentage (TP), and clay ratio (CR).